DAMPAK KOMUNIKASI INTERNAL TERHADAP LOYALITAS KARYAWAN DI INDUSTRI ACARA: STUDI KASUS CV SOUNDTRACK INDONESIA - Anggraini, Meisya; Muhammad Yahyaddin; Muhammad Iqbal (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
This study examines the impact of internal communication on employee loyalty in the event industry. A quantitative associative descriptive approach was employed, with data collected through questionnaires, interviews, and literature review from 33 current and former employees of CV Soundtrack Indonesia using purposive sampling. Data were analyzed using descriptive statistics and simple linear regression analysis. The results indicate that internal communication has a significant and very strong relationship with employee loyalty, with an average internal communication score of 3.94. The regression equation obtained was Y = 1.965+0.465X with a correlation coefficient (R) of 0.945. Internal communication explains 87.7% of employee loyalty, while the remaining 12.3% is influenced by other factors.